Instrumentación y automatización de una sección de un canal de riego abierto en el laboratorio de hidráulica de la Universidad de los Andes (2021)
During this work, the instrumentation of the open irrigation channel of the hydraulics laboratory of the Universidad de los Andes was carried out, specifically, plans, connection diagrams, characterization of level sensors and assemblies of electrovalves and limit switch sensors. In addition, the characterization of the transfer function of the second section of the channel was realized setting the setpoint at 25 cm. Then an On / Off control was developed, a PID controller by the Cohen-Coon method and finally a PI controller by the pole assignment method based on RST control. According to the results obtained in terms of the controllers, the best performance was obtained by the control by assigning poles with an overshoot value of 5.6%, a stabilization time of 65s and steady state error of 0.3716%, according to design parameters. The software used for testing and channel management was TIA Portal V15.